The Effect of Controlled Internal Drug Release (CIDR) on Concentration of Estrogen Hormone in Different Kacang and Bligon Does - Popalaya, Popalaya; Ismaya, Ismaya; Ngadiono, Nono (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
The Effect of Controlled Internal Drug Release (CIDR) on Concentration ofEstrogen Hormone in Different Kacang and Bligon Does